2021
DOI: 10.1002/jia2.25818
|View full text |Cite
|
Sign up to set email alerts
|

Declining HIV incidence in sub‐Saharan Africa: a systematic review and meta‐analysis of empiric data

Abstract: Introduction: UNAIDS models suggest HIV incidence is declining in sub-Saharan Africa. The objective of this study was to assess whether modelled trends are supported by empirical evidence. Methods: We conducted a systematic review and meta-analysis of adult HIV incidence data from sub-Saharan Africa by searching Embase, Scopus, PubMed and OVID databases and technical reports published between 1 January 2010 and 23 July 2019. We included prospective and cross-sectional studies that directly measured incidence f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…Our results indicate that, in a hyperendemic South African setting, incidence was high even among women who reported few individual-level risk factors. Similar gender disparities have been demonstrated across sub-Saharan Africa [ 28 ], and our findings underscore the continuing need for widespread coverage of combination HIV prevention services, especially for women.…”
Section: Discussionsupporting
confidence: 85%
“…Our results indicate that, in a hyperendemic South African setting, incidence was high even among women who reported few individual-level risk factors. Similar gender disparities have been demonstrated across sub-Saharan Africa [ 28 ], and our findings underscore the continuing need for widespread coverage of combination HIV prevention services, especially for women.…”
Section: Discussionsupporting
confidence: 85%
“…Prioritisation does not preclude choice and appropriateness of HIV prevention nor is it a rigid process, but rather a means to allow programme staff and policy makers to maximise the equity, utility, and impact of prevention services. Furthermore, as HIV incidence continues to decline, the importance of prioritisation will increase [ 45 ].…”
Section: The New Target and Approaches For Hiv Preventionmentioning
confidence: 99%
“…Previous studies conducted in other cities in China had shown a pretty high HIV incidence rate among MSM: 6.6 per 100 PY in Hangzhou, 34 6.78 per 100 PY in Yangzhou, 5.77 per 100 PY in Guangzhou, 35 5.3 per 100 PY in Shenyang, 36 5.12 per 100 PY in Nanjing, 37 3.5 per 100 PY in Yunnan 38 and 7.1 per 100 PY in Beijing. 39 The incidence is also at a low level compared with related studies in other regions (sub-Saharan Africa, 40 Latin America 41 and the USA 42–44 ). In this study, the percentage of ‘protective’ and ‘moderate’ behaviour types had a conspicuous growth trend as the follow-up.…”
Section: Discussionmentioning
confidence: 79%